Ensuring safety and improving keeping quality of meatballs by addition of sesame oil and sesamol as natural antimicrobial and antioxidant agents. (October 2021) - Sallam, Khalid Ibrahim; Abd-Elghany, Samir Mohammed; Imre, Kálmán; Morar, Adriana; Herman, Viorel; Hussein, Mohamed Abdallah; Mahros, Mahmoud Ahmed
Abstract: The antioxidant and antimicrobial effect of sesame oil (10, 30, and 50 g/kg) and sesamol (0.1, 0.3, and 0.5 g/kg) in meatballs during cold storage for 18 days at 3 ± 1 °C was investigated. Sesame oil and sesamol did not alter the sensory attributes of meatballs. Addition of either sesame oil or sesamol significantly delayed lipid oxidation when compared with control. Sesamol exhibited more potent antioxidant activities more than sesame oil. During storage, the aerobic plate counts (APCs) and Enterobacteriaceae counts (EBCs) were markedly (P < 0.01) decreased in meatballs treated with sesame oil or sesamol in comparison with untreated control samples. Control meatballs showed signs of quality deterioration at day 7 of storage, while treated meatballs exhibited longer shelf lifes ranged from 9–18 days according to sesame oil or sesamol concentrations. Both sesame oil and sesamol induced marked (P < 0.01) decline in the counts of E . coli O157:H7, Salmonella enterica serovar Typhimurium, Staphylococcus aureus and Listeria monocytogenes that artificially inoculated to meatballs. Sesamol was more effective than sesame oil in the reduction of APCs, EBCs as well as foodborne pathogens. The results suggest that both sesame oil and sesamol are potentially useful natural additives to fresh meat products for improving its microbial quality and extending its shelf life during cold storage. Graphical abstract: Image 1 Highlights: The first time to use sesame oil and sesamol to extend shelf life of meat products. Sesame oil and sesamol exhibited potent antimicrobial effect in meatballs. Sesame oil and sesamol exhibited potent antioxidant effect in meatballs. Sesame oil and sesamol inhibited the growth of inoculated foodborne pathogens. Sesame oil and sesamol extended the shelf life and ensured safety of meat products.